Brain structure in narcissistic personality disorder: A VBM and DTI pilot study. Issue 2 (28th February 2015) - Nenadic, Igor; Güllmar, Daniel; Dietzek, Maren; Langbein, Kerstin; Steinke, Johanna; Gaser, Christian
Abstract: We analysed T1-weighted MRI scans using voxel-based morphometry (VBM) and tract-based spatial statistics (TBBS) on diffusion tensor images (DTI) in narcissistic personality disorder (NaPD) patients and healthy controls. Grey matter deficits include right prefrontal and bilateral medial prefrontal/anterior cingulate cortices, and decreased fractional anisotropy in right frontal lobe white matter. Highlights: First combined grey and white matter analysis in narcissistic personality disorder. Narcissistic personality disorder is associated with frontal grey matter loss. NaPD is also associated with right frontal white matter alterations.